A hidden lethal effect of long microplastic fibres on the coastal copepod Acartia erythraea - Takahashi, Kazutaka; Teh, Jun Chin (Elsevier, 2024)
We investigated the lethal effects of a long fibrous microplastic (the range of lengths, widths, and thicknesses were 1.5–3.6 mm, 10–16 μm, and 7–8.5 μm, respectively) made of polyethylene terephthalate textile, on the marine copepod Acartia erythraea. In laboratory, starved copepods were observed to take in a piece of fibrous microplastic sedimented on the bottom. While no individual ingested the entire fibre, the tip of the ingested fibre reached deep into the gut of the copepods. This suggests that ingestion was not accidental but purposeful behaviour to take in non-living organic matter as a supplementary food source. All copepods that had the fibre in their mouths eventually died within 24-h because the fibre penetrated deep into the gut, preventing feeding and potentially causing stress. Our finding implies that a single piece of microplastic fibre remaining at the bottom of coastal zones could continue to kill copepods owing to its non-degradability.